Sesquiterpenoid Compounds from The Stembark of Aglaia minahassae (Meliaceae) - Nunung Kurniasih; Hersa Milawati; Mohamad Fajar; Ace Tatang Hidayat; Rizky Abdulah; Desi Harneti; Unang Supratman; Mohamad Nurul Azmi (Molekul, 2018)
Two sesquiterpenoid compounds, 4(15)-eudesmen-1b,6a-diol (1) and spathulenol (2) have been isolated from the stembark of Aglaia minahassae belong to Meliaceae family. The chemical structures of 1 and 2 were identified on the basis of spectroscopic evidence including UV, IR, NMR 1D, NMR 2D as well as mass spectra and by comparison with those previously reported spectra data. This compounds were isolated from this plant for the first time.